Perbedaan Hasil Belajar Siswa Melalui Penggunaan Media Alat Laboratorium dengan Media Animasi pada Materi Pokok Suhu dan Kalor - Marwiyah Nst, Masringgit (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to see differences in student learning outcomes through the use of laboratory equipment and amination media on the main topic of Temperature and Heat. This type of research is experimental. The population in the study were all class X students of SMA Medan consisting of 9 classes totaling 417 people. Sampling was carried out using simple random sampling by taking 2 classes from 9 classes randomly, namely class X-9 as experimental class I using laboratory equipment and class X-4 as experimental class II using animation media. Both classes totaled 45 people. The instrument used to determine student learning outcomes is a learning outcomes test in the form of multiple choices with a total of 15 questions. Based on data analysis, it was obtained that the pretest results for both classes were normally distributed and then a data homogeneity test was carried out so that it was known that the two class samples came from homogeneous groups. The post-test results were obtained with an average result for experimental class I which used laboratory equipment media of 59.26 with a standard deviation of 11.21 and experimental class II which used animation media of 54.07 with a standard deviation of 12.81. The results of the t test obtained tcount = 2.04 and ttable = 1.9, so that tcount > ttable (2.04 > 1.9) then H0 was rejected and Ha was accepted, thus it was found that there was a difference in learning outcomes using laboratory equipment and using laboratory media. animation medias